Valorization of Oil Palm Empty Fruit Bunches (OPEFB) for Bioethanol Production in Indonesia - Gozal, Celine; Halim, Amelia; Ridwan, Albert; Wong, Sidney Laura; Young, Kenneth Gabriel; Nataniel, Jocelyn; Kembaren, Riahna (Universitas Negeri Semarang, 2024)
Indonesia, one of the world's largest producers of palm oil, generates large amounts of Oil Palm Empty Fruit Bunches (OPEFB). Its improper disposal can cause air pollution and soil acidification. OPEFB comprises lignocellulose, which can be hydrolyzed into monosaccharides to produce bioethanol. Bioethanol is a versatile product commonly produced using food crops as its raw material, but it can also be produced using lignocellulosic biomass to lessen the competition for food crops and land. Thus, this study aimed to produce bioethanol from OPEFB and enhance its production through adaptive evolution and supplementation with molasses. Adaptive evolution was carried out by exposing the yeast to ethanol concentrations of 3–12% (v/v). Native and adaptive strains are grown in OPEFB media supplemented with PEG and molasses. As a result, bioethanol was successfully produced, reaching around 10% (v/v) using a combination of OPEFB hydrolysate, PEG, and 20% molasses. Moreover, it was found that strains adapted toward 9% ethanol are more resistant to ethanol, as they can grow faster than the native strain. This shows that OPEFB can be effectively valorized for bioethanol production as a solution for OPEFB disposal and establishing a circular economy.